Assessment of factors influencing the success of housing projects in West Pasaman - Ade Herdiwansyah; Denny Helard; Purnawan Purnawan (Trigin Publisher, 2022)
Throughout the nation's journey the property industry has played a very important role in the development and development of the country in the country which has a very large contribution including 9.4 in the national Gross Domestic, and in 2017 the property business has greatly increased up to 15% and has a capacity of Rp. 318 Trillion, this research is to analyze the success factors of housing projects in West Pasaman, how these factors affect the improvement of housing projects in West Pasaman, both from environmental aspects of housing projects, legal aspects of housing projects and economic aspects of housing projects, therefore there are three aspects. Factors that are very influential in terms of the 3 phases of the housing project development process with an assessment taken above 50% as follows; Preconstruction Location selection 57 %, strategic location 80.5%, affordable house selling price 51.3%, licensing 80.9%, marketing marketing 69%. Construction Human resources (workers/carpenters) 71.2%. Post-construction Opportunities for economic growth 87.9%, houses in accordance with the agreement 51.8%, completeness of documents properly taken care of 65.5%.